Sakralitas, Komoditas, dan Konflik: Perdagangan Cendana dan Penyebaran Agama-Agama di Nusa Tenggara Timur - Maulidia Dhuryati Piala Bora; Najamudin M . Lobang (Pustaka Peradaban, 2026)
This study examines the intersection of sacredness, commodity value, and conflict in the sandalwood trade and its influence on the spread of Islam, Catholicism, and Protestantism in East Nusa Tenggara (NTT). Historically regarded as a sacred material in local traditions and global religious practices, sandalwood became a highly valued commodity in Asian and European trade networks from the tenth to the seventeenth century. The fusion of ritual significance and economic value generated contestation among local elites, Muslim traders, and colonial powers such as the Portuguese and the Dutch, each seeking control over this strategic resource. Previous studies largely emphasize political-economic aspects, while research on the role of sandalwood in shaping religious dynamics remains limited. Using a qualitative-historical approach and Johan Galtung’s theoretical framework, this study analyzes forms of structural and cultural violence, as well as the competing interests embedded in the sandalwood trade. The findings indicate that sandalwood facilitated the entry and growth of Islam through commercial interactions, while the spread of Catholicism and Protestantism was strengthened by colonial political agendas. This study argues that the commodification of sandalwood not only structured economic and political relations but also significantly influenced patterns of social interaction and religious transformation in NTT. Penelitian ini mengkaji hubungan antara sakralitas, komoditas, dan konflik dalam perdagangan cendana serta pengaruhnya terhadap penyebaran Islam, Katolik, dan Protestan di Nusa Tenggara Timur (NTT). Cendana, yang secara historis memiliki nilai ritual dalam tradisi lokal dan agama-agama dunia, sejak abad ke-10 hingga ke-17 berkembang menjadi komoditas yang sangat bernilai dalam jaringan perdagangan Asia dan Eropa. Perpaduan nilai sakral dan ekonomi ini memicu kontestasi antara elit lokal, pedagang Muslim, serta kekuatan kolonial Portugis dan Belanda yang berupaya menguasai sumber daya strategis tersebut. Penelitian terdahulu umumnya berfokus pada aspek ekonomi-politik, sedangkan kajian mengenai peran cendana dalam dinamika keagamaan masih terbatas. Dengan menggunakan pendekatan kualitatif-historis dan kerangka teori Johan Galtung, penelitian ini menganalisis bentuk kekerasan struktural dan kultural serta kontradiksi kepentingan yang muncul dari penguasaan cendana. Temuan penelitian menunjukkan bahwa perdagangan cendana menjadi medium penting dalam masuk dan berkembangnya Islam melalui hubungan dagang, sementara penyebaran Katolik dan Protestan diperkuat oleh dukungan politik kolonial. Studi ini menegaskan bahwa komodifikasi cendana tidak hanya membentuk struktur ekonomi-politik, tetapi juga memengaruhi pola interaksi dan transformasi keagamaan di NTT.